The role of polymer matrices and compositions - Perry Law, Nyuk Khui; Md. Rezaur, Rahman; Muhammad Khusairy, Bakri (Woodhead Publishing / Elsevier Ltd., 2026)
This chapter discusses a range of conventional and biodegradable polymer matrices and their role in conventional polymer and biocomposite material development. The composition part of this chapter focuses mostly on the weightage variation affecting the properties of the composite. For simplicity, only the mechanical properties and optimal weightage are selected and discussed to showcase the capabilities of the composite materials. Overall, this chapter may assist researchers in understanding the role of polymer matrices and compositions related to conventional polymer and biocomposite development.